Interventional cardiology and cardiac catheterisation : the essential guide - Boland, John, MSc; Muller, David W. M. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Cardiology is becoming an increasingly complex field understood by only a select group of medical specialists. This publication demystifies many difficult topics in interventional cardiology and cardiac catheterisation, commencing with the basics of laboratory instrumentation and technology and progressing to a comprehensive review of both new and established cardiac interventions. Unlike other publications that are directed mainly towards clinicians, this text is specifically written to assist newcomers such as such as medical trainees, nurses, technicians, scientific staff and other allied health professionals understand the wonders of interventional cardiology, and includes extensive explanations of the techniques of angiography, and new percutaneous. The comprehensive information presented herein, written by recognised specialists in their respective fields, will no doubt prove of great benefit to clinician and non-medical specialist alike.
Preceded by Cardiology and cardiac catheterisation : the essential guide / edited by John Boland and David W.M. Muller. 2001.
OCLC-licensed vendor bibliographic record.
Keywords: Cardiac catheterization; Cardiology; MEDICAL / General; MEDICAL / Cardiology; MEDICAL / Radiology & Nuclear Medicine